PERBANDINGAN EFEKTIVITAS EKSTRAK KULIT BATANG KAYU SRIKAYA DENGAN BIJI BUAH SRIKAYA (Annona squamosa L.) TERHADAP KEMATIAN JENTIK NYAMUKAedes aegypti - Abdul Syukur; Tri Fatmawati, Hajimi (Jurnal Kesehatan, 2025)
Comparison Of The Effectiveness Of Sugar Apple Trunk Bark With Sugar Apple Seeds (Annona Squamosa L.) On Death Of Aedes Aegypti Mosquito. Vector control aims to reduce the risk of transmitting Dengue Hemorrhagic Fever (DHF). In order to minimize the reproduction of the Aedes Sp mosquito vector, it is necessary to break the chain from the condition where the mosquito is still a larva. In connection with this, efforts are needed to obtain alternative insecticides that are natural and decompose in nature, and are safe for the environment, namely using plants that contain natural insecticides, one of which is the sugar apple plant (Annona squamosa L.). This research method is quasi-experimental research with Nonequivalent Control Group Design. The Aedes aegypti mosquito larvae were divided into 2 groups, the group that would be tested to compare sugar apple bark extract with sugar apple seeds and a control group without treatment. Mann-Whitney test results ｐvalue = 0.876 (> α/0.05) or there is no significant difference between sugar apple bark extract and sugar apple seed extract on larval death. The results of tests in the laboratory showed that the bark extract of srikaya had the effect of causing 89.6% larval death, while the srikaya fruit seed extract had the effect of causing 100% larval death, so it could It was stated that srikaya fruit seed extract was more effective in killing Aedes aegypti mosquito larvae. The conclusion of this research is that there is a difference in effectiveness between sugar apple bark extract and sugar apple seed extract on the death of Aedes aegypti larvae.